Awareness, Attitude and Practice of Infection Control Among Clinical Year Medical Students of a Private Medical School in Malaysia - Sandheep Sugathan (Journal of Global Pharma Technology, 2019)
Objectives: The current research was planned to evaluate the awareness, attitude and practice of infection control among the clinical year medical students of a private medical school in Ipoh city, Perak State of Malaysia. This study was also aimed at any need for improving the curriculum in relation to infection control measures with an eye on reducing hospital acquired infections in future. Methods: This cross-sectional descriptive study on the awareness, attitude and practice on infection control was conducted among clinical year medical students from a private medical school in Malaysia, using a self-administered questionnaire. Results: Our study revealed that those clinical students with higher levels of attitude showed a significantly higher level of practice (p-value <0.001). The respondents having good knowledge, good attitude and correct practice were 66.7%, 57.6% and 51.5% respectively. Conclusion: Awareness of clinical medical students on infection control was quite good in this research, but it was not reflecting on attitude level and practice levels of students. There was a significant association between attitude level and practice. Gender and years of exposure in clinical practice were not significant predictors.